AB0548 Sapho syndrome and inflammatory bowel disease: systematic review. (23rd January 2014) - Naves, J. E.; Martínez-Morillo, M.; Cabré, E.; Mañosa, M.; Domènech, E.; Tejera Segura, B.; Grados, D.; Holgado, S.; Mateo, L.; Olivé, A.
Abstract : Background: The association of the SAPHO syndrome and inflammatory bowel disease (IBD) was first reported in 1992. To date, only case reports and short series have been published. Objectives: To report three new cases and systematically review the literature on this association. Methods: All patients with concomitant diagnosis of SAPHO syndrome and IBD were identified from the databases of the Rheumatology and Gastroenterology departments of our institution, which has a reference area of 800000 inhabitants. In addition, we systematically searched for published full articles in Medlars Online International Literature (MEDLINE) via PubMed. Relevant information of each positive match was collected and all authors were contacted for additional clinical data. Results: Three patients sharing both SAPHO syndrome and IBD were identified among the 62 patients with SAPHO syndrome (4.8% of the SAPHO cohort) and among 1, 309 patients with IBD (0.2% of the IBD cohort) from our hospital database. After a systematic review, others 36 cases with concomitant diagnosis of IBD and SAPHO syndrome or its variant chronic recurrent multifocal osteomyelitis (CRMO) were identified. There was a female predominance (64%) and an early age of onset of both diseases (24 years for SAPHO syndrome and 18 years for IBD). SAPHO diagnosis preceded IBD diagnosis in 55% of cases, being simultaneous or subsequent in the rest. A high proportion of patients presented Crohn's disease (69%) with colonic involvement. The most frequent osteoarticular locations were peripheral joints (61%); anterior chest wall (56%), sacroiliac joint (20%), y spine (18%). Approximately 41% of cases developed typical SAPHO skin manifestations, being palmoplantar pustolosis the most common. The most common treatment for IBD of the subgroup of cases published after year 2000 were corticosteroids (68%), aminosalicylates (52%), immunossupresors (37%), anti-TNF (16%); and for SAPHO syndrome NAIDs (63%), corticosteroids (37%); aminosalicylates (31%), immunossupresors (21%), pamidronate (16%) y anti-TNF (16%). Conclusions: SAPHO syndrome seems to precede IBD. It is more frequent in females and at early ages. Crohn's disease is more associated to SAPHO than ulcerative colitis. Interestingly enough colic involvement is more frequent. Both diseases respond well to the same treatments but NAIDs should be avoided because their potential risk of triggering a flare of IBD. Disclosure of Interest: None Declared